Crystal Structure and Magnetic Susceptibility of Iron Sand From Pangeo Village, Morotai Jaya Subdistrict as The Cathode of Lithium-Ion Batteries - Rahim Achmad; Suryani Taib; Rohima Wahyu Ningrum (TECHNO: JURNAL PENELITIAN, 2022)
Morotai Island has a wealth of iron sand which is a natural resource in Morotai Jaya District, Pangeo Village. The utilization of iron sand is still for local community building materials. The purpose of this study was to determine the structure and magnetic susceptibility of iron sand as a basic material for cathode materials in the manufacture of lithium-ion batteries (LIB). The research sample was taken randomly, then it was prepared in the laboratory to obtain dry-phase iron sand. After being tested using an XRD tool, namely samples A, E, and I, it was found that there was a lot of Fe3O4 contained in iron sand. The diffraction peaks indicate Fe3O4 material with an inverse spinel structure. Sample A is the most crystalline compared to sample I. Sample E has the lowest diffraction peak pattern due to the dominant mineral hematite (Fe2O3) 70.31%. The value of the BSM test obtained the greatest magnetic susceptibility of 82867.54x10-8m3 /kg. The smallest is in sample J with a value of 13186.98 54x10-8m3 /kg because during synthesis it is slightly attracted by magnets and the color is not too black which mixes a lot with other materials. In addition, this relationship is directly proportional to sample E which contains the magnetic material Fe2O3 of the characterization of 70.31. The range of magnetic susceptibility values in samples A to L is in the interval (46 – 80,000) x 10-8m3/kg, and (20,000 - 110,000) x 10-8m3/kg. Based on this interval, both magnetic and mass susceptibility of each iron sand sample contained ilmenite (FeTiO3) particles in the antiferromagnetic group and magnetite (Fe3O4) in the ferromagnetic group.